2015
DOI: 10.1007/s10811-015-0690-6
|View full text |Cite
|
Sign up to set email alerts
|

Alpha-amylase, antioxidant, and anti-inflammatory activities of Eucheuma denticulatum (N.L. Burman) F.S. Collins and Hervey

Abstract: Eucheuma denticulatum is a red edible seaweed that grows in the East Malaysia coastal region. The objective of this study was to investigate the α-amylase, antioxidant and anti-inflammatory activities of E. denticulatum ethanol extract and its three fractions (n-hexane, ethyl acetate and acetone). α-Amylase activity was assessed by dinitrosalicylic acid (DNS) assay, while the antioxidant property was determined by oxygen radical absorbance capacity (ORAC) analysis. The anti-inflammatory effects of the seaweed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…Also, this red seaweed is cultivated for its hydrocolloids (Santos, 1989). In addition, it contains high amounts of dietary fibers, minerals, vitamins, antioxidants, polyphenols, phytochemicals, proteins, and polyunsaturated fatty acids (Matanjun et al, 2009;Balasubramaniam et al, 2016;Wardani et al, 2017). Eucheuma species traditionally used in Chinese herbal medicine to treat goiter, cough, bronchitis, tonsillitis, asthma with excessive phlegm, stomach ailments, hemorrhoids and anal fistulas (Chengkui and Junfu, 1984).…”
Section: Introductionmentioning
confidence: 99%
“…Also, this red seaweed is cultivated for its hydrocolloids (Santos, 1989). In addition, it contains high amounts of dietary fibers, minerals, vitamins, antioxidants, polyphenols, phytochemicals, proteins, and polyunsaturated fatty acids (Matanjun et al, 2009;Balasubramaniam et al, 2016;Wardani et al, 2017). Eucheuma species traditionally used in Chinese herbal medicine to treat goiter, cough, bronchitis, tonsillitis, asthma with excessive phlegm, stomach ailments, hemorrhoids and anal fistulas (Chengkui and Junfu, 1984).…”
Section: Introductionmentioning
confidence: 99%
“…To date, information regarding the bioactive components present in the Malaysian local seaweeds remain insufficient. The current work is a continuation of our previous research [ 4 , 5 ]. These studies reported that the ethanol extracts of E. denticulatum manifest anti-diabetic, anti-obesity and anti-inflammatory properties.…”
Section: Introductionmentioning
confidence: 70%
“…The seaweeds ( E. denticulatum, S. polycystum and C. lentillifera ) were collected from the coast of Sabah with the assistance of the Aquaculture Division, Department of Fisheries, Malaysia. Samples were processed immediately upon arrival at the Institute for Medical Research, Malaysia, as previously discussed [ 4 , 5 ]. Briefly, the collected seaweed samples were cleaned thoroughly to remove epiphytes, salt and sand using tap water and finally rinsed with deionized water three times before being cut into small pieces.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, many studies have been reported other functionality of secondary metabolites from E. spinosum which could be a potential source. The secondary metabolites are used as an anti-oxidative compound [9,10,11,12], anti-bacterial [13], anti-tumor [14], anti-hypercholesterolemic [15], anti-inflammation and amylase inhibition activity [16]. The secondary metabolite compounds contained in E. spinosum are alkaloids [17], flavonoids [13], isoprenoid [18], monoterpene [19], diterpene [20], and myrcene [21].…”
Section: Introductionmentioning
confidence: 99%